Model Perencanaan Strategis Sistem Informasi Pendidikan Menggunakan Ward-Peppard - Imam Hizbullah (Peneliti.net, 2020)
This Research is proposes an information system implementation strategy in the educational field to encourage a more competitive direction. In planning an information system strategy a framework of reference is needed in preparing it so it can be aligned with the business needs of the institution. The method developed by Ward-Peppard is one of the frameworks that are often used in the preparation for strategy information systems planning. In this research the ward-peppard method is used along with the SWOT analysis tool, PEST in it. The results of this research indicate 11 information system candidates mapped in Mc Farlan's portfolio as a development priority to achieve the business goals of SMA Muhammadiyah 1 Morotai Island